The Use of Mobile Learning in Elementary School: Is It Important? - Indra Perdana; Siti Aisyah; Pandu Adi Cakranegara; Zain Ahmad Fauzi; Dina Destari (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study describes the use of mobile learning technology for students at the elementary school level. There are many educational applications, so researchers want to know whether these applications are needed for education. In this study, in order to understand how students, understand the use of educational applications that can be used on mobile devices, a qualitative method is used. Researchers in this case also use data collection techniques by conducting semi-structured interviews with students and elementary school students who use cellular technology in learning activities. The children said that using instructional apps had helped them improve their skills. When they work in groups, they develop relational and communication skills. On the other hand, there are some students who do not see the value or convenience of using educational apps on their mobile devices. The result of this research is the application of arithmetic and storytelling helps children improve their cognitive abilities. At the same time, when they interact with others, this activity stimulates them and offers emotional benefits. Use Study participants demonstrated a wide range of learning skills and capacities, as demonstrated by this study. Finally, this work offers new possibilities for future research in this exciting field.